Solutions like excitations in the one-dimensional electrical transmission line - Pelap, F.B.; Faye, M.M. (Нелінійні коливання, 2005)
Dynamics of modulated waves are studied in the one-dimensional discrete nonlinear electrical transmission line. Contribution of the linear dispersive capacitance is appreciated and it is shown via a reductive perturbation method that evolution of such waves in this system is governed by a higher order nonlinear Schrodinger equation. Passing through the Stokes analysis, a generalized criterion for the Benjamin ¨ – Feir instability in the network is established and the exact solutions of the obtained wave equation are determined by the means of the Pathria and Morris’s approach.